ETHICS IN CHILD PROGRAM IMPRESSIONS ON TELEVISION - Natalia, El Chris (Academic Research Centre Services, 2015)
Although nowadays the new media comes to exist in the society, the conventional media like television is still be a part of Indonesian society, especially is the areas that is untouched  by the internet. Television still has its own audience. Television is obliged to perform its functions in providing information, educate, entertain, control and also as a social adhesive. Children as one of television audiences always get more attention because children are the next generation who are very easily influenced by this audiovisual media. Children are the easiest figure to imitate what they see on television. Ethics in children's program broadcasted in television is important to avoid the damage of children development in both psychologically and physically.